Analysis of two dimensional CFD modeling and simulation inside lemang oven during cooking - Nurul Fariza Mohamed Elias (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
Experimental testing is carried out to discover the temperatures at the certain oven surface at the certain times. This steps required because to compare the result of analysis by using CFD with the experimental result.